Hard X‐Ray Nanoholotomography: Large‐Scale, Label‐Free, 3D Neuroimaging beyond Optical Limit. Issue 6 (30th March 2018) - Khimchenko, Anna; Bikis, Christos; Pacureanu, Alexandra; Hieber, Simone E.; Thalmann, Peter; Deyhle, Hans; Schweighauser, Gabriel; Hench, Jürgen; Frank, Stephan; Müller‐Gerbl, Magdalena; Schulz, Georg; Cloetens, Peter; et al.
Abstract: There have been great efforts on the nanoscale 3D probing of brain tissues to image subcellular morphologies. However, limitations in terms of tissue coverage, anisotropic resolution, stain dependence, and complex sample preparation all hinder achieving a better understanding of the human brain functioning in the subcellular context. Herein, X‐ray nanoholotomography is introduced as an emerging synchrotron radiation‐based technology for large‐scale, label‐free, direct imaging with isotropic voxel sizes down to 25 nm, exhibiting a spatial resolution down to 88 nm. The procedure is nondestructive as it does not require physical slicing. Hence, it allows subsequent imaging by complementary techniques, including histology. The feasibility of this 3D imaging approach is demonstrated on human cerebellum and neocortex specimens derived from paraffin‐embedded tissue blocks. The obtained results are compared to hematoxylin and eosin stained histological sections and showcase the ability for rapid hierarchical neuroimaging and automatic rebuilding of the neuronal architecture at the level of a single cell nucleolus. The findings indicate that nanoholotomography can complement microscopy not only by large isotropic volumetric data but also by morphological details on the sub‐100 nm level, addressing many of the present challenges in brain tissue characterization and probably becoming an important tool in nanoanatomy. Abstract : Overcoming optical or electron microscopy limitations, X‐ray nanoholotomography is introduced as an emerging technology for large‐scale, label‐free, nondestructive neuroimaging with isotropic voxel sizes down to 25 nm, exhibiting a spatial resolution of 88 nm. The obtained results showcase the ability for rapid neuroimaging beyond the optical limit and automatic rebuilding of neuronal architecture.